Validity Of Imla Exercise Book Based On Bloom's Cognitive Taxonomy For STIBA Ar-Raayah Sukabumi Language Preparation Students - Jannah, Nidaul; bahruddin, Uril; Hasan, Nur; Muhammad, Abdul Halim; Al Faiz, Musa (Ukazh: Journal of Arabic Studies, 2025)
The purpose of this study was to analyze the need for an Imla Exercise book based on Bloom's cognitive classification because the exercises in the textbooks were not enough, and the lack of diversity of the exercises, and the imla rules and errors in writing among students. Researchers used a qualitative and quantitative approach, a development approach, the method used was the ADDIE method in the preparation of the Imla Exercise book, and the sources and data came from interviews and questionnaires, analysis with data collection, classification, data presentation and conclusions. The results showed that the preparation of the exercise book was carried out through several stages. First, a student needs analysis was conducted to identify aspects that needed to be improved. Second, the exercise book was designed according to the results of the analysis. Third, the development stage was carried out by applying the previously planned design. Fourth, the book was evaluated by experts. Finally, revisions were made based on the suggestions given by the experts before the final product was declared valid. The validity of the brochure was measured by the percentage of the three expert evaluations: 92.2% and from the Likert classification scale shows that the product is at an excellent level, which can be used without modification.